Membaca Liquid Society dari Perspektif Burnout Society - Kuntag, Paulina; Ohoitimur, Johanis (Media: Jurnal Filsafat dan Teologi, 2025)
This article synthesizes the ideas of Bauman and Byung-Chul Han regarding the social transformation of modern society. Bauman posits that postmodern society exists in a state of constant flux, leading to the creation of what he terms as a "liquid society." The dynamic and ever-changing nature of this society gives rise to an unstable sense of self (referred to as a "liquid identity"). Bauman attributes this fluidity to the continuous industrial market changes that generate novelty. In contrast, Byung-Chul Han observes that contemporary society in the 21st century is grappling with a severe form of pathology. This achievement-oriented society is overwhelmed by a profound exhaustion resulting from the culture of self-exploitation prevalent within it. Han labels this society as a "burnout society" characterized by a prevalence of neurological and mental disorders such as Autoimmune, Depression, Bipolar, and ADHD. People in this society engage in self-exploitation as they are unable to engage in contemplation, becoming both masters and slaves of their own actions. Critiques of the concepts of liquid society and burnout society have been raised. The hypothesis presented in this article suggests that the complexities of burnout society are rooted in liquid society.